Comparative transcriptomics reveals conserved infection-associated gene expression in Phytophthora agathidicida across its natural gymnosperm host kauri and the model angiosperm host Nicotiana benthamiana - Rosie E. Bradshaw; Jason B. Shiller; Yanan Guo; Mariana Tarallo; Scott J. Heslop; Rebecca L. McDougal; Preeti Panda; Nari M. Williams; Carl H. Mesarich (Fungal Biology, 2026)

Recent physiological, genetic, and management perspectives on lodging resistance in rice - Ranjan Kumar Jena; Baneeta Mishra; Soumya Mohanty; Nalini Kanta Choudhury; Swagatika Das; Darshan Panda; Nitish Kumar Jena; Abinash Mishra; Amrita Sharma; B. N. Devanna; Rameswar Prasad Sah; Awadesh Kumar; et al. (Planta, 2026)

Transcriptomic and Hormonal Regulation of Rice Defence Against Brown Planthopper - Guru-Pirasanna-Pandi Govindharaj; Rudramadhab Panda; Kutubuddin Molla; Romio Saha; Mridul Chakroborti; Meera Kumari Kar; C. Parameswaran; S. Raghu; B. Parameswari; S. D. Mohapatra (Journal of Crop Health, 2026)

Toward efficient simulation of cracked 3D-printed concrete beams: Analytical and homogenized finite element approach - S. Sai Kumar; L. Kumar; N. Muthu; B. Panda (Engineering Structures, 2026)

Rare beaching event of the neustonic blue dragon (Glaucus atlanticus) and blue button jellyfish (Porpita porpita) along the Odisha coast, India - Panda Narayan; K. U. Abdul Jaleel; V. B. Adarsh; R. Jyothibabu (Aquatic Ecology, 2026)

Estimation of Daily Reference Evapotranspiration Using Machine Learning and Deep Learning Techniques with Sparse Meteorological Data - Ajit Kumar Nayak; A. Sarangi; S. Pradhan; R. K. Panda; N. M. Jeepsa; B. S. Satpathy; Mithlesh Kumar (Agricultural Research, 2026)

Identifying potent inhibitors for Mycobacterium tuberculosis MabA (FabG1) - Debashis Panda; Jitendra Maharana; Arjun Sharma; Sachin B. Wadavrao; Abhishek Chowdhury; Monjur Ahmed Laskar; Mahendra K. Modi; Manabendra D. Choudhury (Molecular Diversity, 2026)

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

Design of a Multi-Epitope Vaccine using β-barrel Outer Membrane Proteins Identified in Chlamydia trachomatis - Amisha Panda; Jahnvi Kapoor; B. Hareramadas; Ilmas Naqvi; Satish Ganta; Ravindresh Chhabra; Sanjiv Kumar; Anannya Bandyopadhyay (The Journal of Membrane Biology, 2025)

Distribution and Strandings of Risso’s Dolphin ( Grampus griseus (G. Cuvier, 1812)): First Sighting From the Bay of Bengal Inside the Indian EEZ - Yosuva Mariasingarayan; John Peter Raju; Kumar Pandion; Shruti Nair; Ayana Sholy; Ashish P. Jacob; Soumya Ranjan Panda; Nishant Umralkar; B. Arunima; Nidhi Johri; Lekkala Ramajyothi Madhavi; P. S. Ashik; et al. (Marine Mammal Science, 2025)

Correlation awareness evolutionary sparse hybrid spectral band selection algorithm to detect aflatoxin B1 contaminated almonds using hyperspectral images - Md. Ahasan Kabir; Ivan Lee; Chandra B. Singh; Gayatri Mishra; Brajesh Kumar Panda; Sang-Heon Lee (Food Chemistry, 2025)

Habitat-dependent dietary pattern of white-bellied sea-eagle: a cross-regional meta-analysis - Sakti Prasad Pattnayak; Aditya K. Panda; B. Anjan Kumar Prusty; Sandeep Rout; Priyanka Jena (Ornithology Research, 2025)

Recent trends of machine learning on energy storage devices - Arpit B. Mendhe; Himanshu Sekhar Panda (Next Research, 2025)

Recent advances on artificial intelligence-based approaches for food adulteration and fraud detection in the food industry: Challenges and opportunities - Puja Das; Ammar B. Altemimi; Pinku Chandra Nath; Mehak Katyal; Radha krishnan Kesavan; Sarvesh Rustagi; Jibanjyoti Panda; Satya Kumar Avula; Prakash Kumar Nayak; Yugal Kishore Mohanta (Food Chemistry, 2025)

Genome-wide association study reveals effect of nsSNPs on candidate genes in rice during iron deficiency - Siddharth Panda; Annamalai Anandan; K. Mohamed Shafi; Mahantesha B. N. Naika; R. Sowdhamini; G. Vanishree; Sutapa Sarkar; Anthony J. Travis; Gareth J. Norton; Adam H. Price (Functional & Integrative Genomics, 2024)

The genus Bothriochloa (Poaceae: Andropogoneae) in Odisha: with an addition of species Bothriochloa kuntzeana (Hack.) Henrard - P. R. Mane; J. Swamy; S. P. Panda; P. K. Kamila; V. K. Mastakar; G. G. Potdar; C. B. Salunkhe (Vegetos, 2024)

Seasonal abundance of Hyalomma anatolicum tick infesting cattle of coastal Odisha, India - M. Dehuri; M. R. Panda; B. N. Mohanty; N. Sahoo; P C Behera; A. K. Kundu; S. K. Panda (International Journal of Tropical Insect Science, 2024)

Rice-based integrated farming system improves the soil quality, bacterial community structure and system productivity under sub-humid tropical condition - Prafulla Kumar Nayak; A. K. Nayak; B. B. Panda; A. Senapati; P. Panneerselvam; A. Kumar; R. Tripathi; A. Poonam; M. Shahid; S. D. Mohapatra; Megha Kaviraj; Upendra Kumar (Environmental Geochemistry and Health, 2024)

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Agronomic manipulation in main season and ratoon rice influences growth, productivity, and regeneration ability in tropical lowlands - B. Lal; Priyanka Gautam; A.K. Nayak; R. Raja; B.B. Panda; R. Tripathi; M. Shahid; D. Chatterjee; P. Bhattacharyya; P. Bihari; Teekam Singh; S.K. Meena; et al. (Field Crops Research, 2023)

Mild-temperature Organosolv treatment of rice-straw: extracting ability of dimethylformamide and material applications - B. B. Kanrar; S. Singh; S. K. Pal; D. Panda (International Journal of Environmental Science and Technology, 2023)

Modeling and prediction of fire occurrences along an elevational gradient in Western Himalayas - Somnath Bar; Bikash Ranjan Parida; Arvind Chandra Pandey; B. Uma Shankar; Pankaj Kumar; Santosh K. Panda; Mukunda Dev Behera (Applied Geography, 2023)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Molecular Evidence and Sequence Analysis of Goatpox Virus Isolates from Assam, India: An Emerging Viral Disease of Goats - D. P. Bora; G. Venkatesan; S. Arya; A. O. Pariat; Amit Kumar; Sabnam Ingtipi; Puja Mech; G. B. Manjunatha Reddy; Shyama P. Panda; N. N. Barman; V. Balamurugan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Comparative analysis of the immunomodulatory potential of caprine fetal adnexa derived mesenchymal stem cells - Anjali Somal; Irfan A. Bhat; Sriti Pandey; Mohd Matin Ansari; B. Indu; Bibhudatta S. K. Panda; Mukesh Kumar Bharti; Vikash Chandra; G. Saikumar; G. Taru Sharma (Molecular Biology Reports, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Discovery of genomic regions and candidate genes for grain weight employing next generation sequencing based QTL-seq approach in rice (Oryza sativa L.) - Reddyyamini Bommisetty; Navajeet Chakravartty; Reddaiah Bodanapu; Jeevula B. Naik; Sanjib K. Panda; Sivarama P. Lekkala; Krishna Lalam; George Thomas; S. J. Mallikarjuna; G. R. Eswar; Gopalakrishna M. Kadambari; Swarajyalakshmi N. Bollineni; et al. (Molecular Biology Reports, 2020)

Quantification of recharge from the rainwater harvesting structures—a case study in hard rock area of Odisha (India) - Ranu Rani Sethi; S. K. Ambast; B. Panda; M. Das (Sustainable Water Resources Management, 2020)

Molecular and phylogenetic analysis of the dengue strains circulating in Odisha, India - J. Sabat; S. Subhadra; B. Thakur; M. Panda; S. Panda; S. S. Pati; L. M. Ho; S. Dixit; S. K. Rathore; S. K. Kar; B. Dwibedi (VirusDisease, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Inter-relationship between intercepted radiation and rice yield influenced by transplanting time, method, and variety - Priyanka Gautam; B. Lal; A. K. Nayak; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; U. Kumar; M. J. Baig; D. Chatterjee; C. K. Swain (International Journal of Biometeorology, 2019)

First record of Metanophrys sinensis (Protozoa: Ciliophora: Scuticociliatida) from India causing large scale mortality in a new host Macrobrachium rosenbergii larvae - P K Sahoo; S Pattanayak; A Paul; M K Sahoo; P Rajesh Kumar; D Panda; B R Pillai (Journal of Fish Diseases, 2018)

Measuring potassium fractions is not sufficient to assess the long-term impact of fertilization and manuring on soil’s potassium supplying capacity - Debarup Das; Amaresh Kumar Nayak; V. K. Thilagam; Dibyendu Chatterjee; M. Shahid; Rahul Tripathi; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; B. B. Panda; S. S. Biswas (Journal of Soils and Sediments, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Balkrishna A. Shinde; Bhushan B. Dholakia; Khalid Hussain; Sayantan Panda; Sagit Meir; Ilana Rogachev; Asaph Aharoni; Ashok P. Giri; Avinash C. Kamble (Plant Molecular Biology, 2017)

Submergence Induced Tiller Mortality and Yield Reduction in Rice Can be Minimized Through Post-submergence Nitrogen Application - Priyanka Gautam; B. Lal; R. Raja; B. B. Panda; R. Tripathi; M. Shahid; S. Mohanty; S. Maharana; A. K. Nayak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Circulating genotypes of Pneumocystis jirovecii and its clinical correlation in patients from a single tertiary center in India - Y. Singh; B. R. Mirdha; R. Guleria; S. Khalil; A. Panda; R. Chaudhry; A. Mohan; S. K. Kabra; L. Kumar; S. K. Agarwal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Multitier agroforestry system for integrated resource conservation on uplands of Eastern Ghats region in India - Praveen Jakhar; Anchal Dass; Partha Pratim Adhikary; S. Sudhishri; B. S. Naik; H. C. Hombegowda; M. Madhu; N. K. Lenka; P. R. Chaudhary; R. K. Panda (Agroforestry Systems, 2017)

A study of 2014 record drought in India with CFSv2 model: role of water vapor transport - S. S. V. S. Ramakrishna; V. Brahmananda Rao; B. R. Srinivasa Rao; D. Hari Prasad; N. Nanaji Rao; Roshmitha Panda (Climate Dynamics, 2017)

Way forward to achieve sustainable and cost-effective biofuel production from microalgae: a review - N. Misra; P. K. Panda; B. K. Parida; B. K. Mishra (International Journal of Environmental Science and Technology, 2016)

Micropropagation of Semecarpus anacardium L. from mature tree-derived nodal explants - B. M. Panda; U. J. Mehta; S. Hazra (Plant Biosystems, 2016)

Effect of Supplementing Organic Forms of Zinc, Selenium and Chromium on Performance, Anti-Oxidant and Immune Responses in Broiler Chicken Reared in Tropical Summer - S. V. Rama Rao; B. Prakash; M. V. L. N. Raju; A. K. Panda; R. K. Kumari; E. Pradeep Kumar Reddy (Biological Trace Element Research, 2016)

Radio-tolerance of finger millet Eleusine coracana (L.) Gaertn cultivars to ionizing radiation - A. Venugopal; Dambaru Golari; P. Venu-Babu; Rakesh K. Singhal; Brahma B. Panda (The Nucleus, 2016)

Characterizing spatial variability of soil properties in salt affected coastal India using geostatistics and kriging - Rahul Tripathi; A. K. Nayak; Mohammad Shahid; R. Raja; B. B. Panda; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; R. N. Sahoo (Arabian Journal of Geosciences, 2015)

Impairment of soil health due to fly ash-fugitive dust deposition from coal-fired thermal power plants - R. Raja; A. K. Nayak; A. K. Shukla; K. S. Rao; Priyanka Gautam; B. Lal; R. Tripathi; M. Shahid; B. B. Panda; A. Kumar; P. Bhattacharyya; G. Bardhan; et al. (Environmental Monitoring and Assessment, 2015)

Novel lead generation of an anti-tuberculosis agent active against non-replicating mycobacteria: exploring hybridization of pyrazinamide with multiple fragments - Shankar D. Markad; Parvinder Kaur; B. K. Kishore Reddy; Murugan Chinnapattu; Anandkumar Raichurkar; Radha Nandishaiah; Manoranjan Panda; Pravin S. Iyer (Medicinal Chemistry Research, 2015)

Long-term effect of rice-based farming systems on soil health - Priyanka Bihari; A. K. Nayak; Priyanka Gautam; B. Lal; M. Shahid; R. Raja; R. Tripathi; P. Bhattacharyya; B. B. Panda; S. Mohanty; K. S. Rao (Environmental Monitoring and Assessment, 2015)

Oxidative stress and non-linear threshold (NLT) genotoxic dose responses to ionizing radiation in niger, Guizotia abyssinica (L.f.) Cass - Dambaru Golari; A. Venugopal; P. Venu-Babu; Rakesh K. Singhal; Brahma B. Panda (The Nucleus, 2014)

Seasonal trends, meteorological impacts, and associated health risks with atmospheric concentrations of gaseous pollutants at an Indian coastal city - Parth Sarathi Mahapatra; Sipra Panda; P. P. Walvekar; R. Kumar; Trupti Das; B. R. Gurjar (Environmental Science and Pollution Research, 2014)

Soil respiration, labile carbon pools, and enzyme activities as affected by tillage practices in a tropical rice–maize–cowpea cropping system - S. Neogi; P. Bhattacharyya; K. S. Roy; B. B. Panda; A. K. Nayak; K. S. Rao; M. C. Manna (Environmental Monitoring and Assessment, 2014)

Effect of Fly Ash Deposition on Photosynthesis, Growth and Yield of Rice - R. Raja; A. K. Nayak; K. S. Rao; Chandrika Puree; Mohammad Shahid; B. B. Panda; Anjani Kumar; R. Tripathi; P. Bhattacharyya; M. J. Baig; B. Lal; Sangita Mohanty; et al. (Bulletin of Environmental Contamination and Toxicology, 2014)

Fly Ash Addition Affects Microbial Biomass and Carbon Mineralization in Agricultural Soils - A. K. Nayak; Anjani Kumar; R. Raja; K. S. Rao; Sangita Mohanty; Mohammad Shahid; Rahul Tripathy; B. B. Panda; P. Bhattacharyya (Bulletin of Environmental Contamination and Toxicology, 2014)

Biodegradation of phenol by mixed microbial culture: an eco-friendly approach for the pollution reduction - T. Senthilvelan; J. Kanagaraj; Rames C. Panda; A. B. Mandal (Clean Technologies and Environmental Policy, 2014)

Elucidation of lead-induced oxidative stress in Talinum triangulare roots by analysis of antioxidant responses and DNA damage at cellular level - Abhay Kumar; M. N. V. Prasad; V. Mohan Murali Achary; Brahma B. Panda (Environmental Science and Pollution Research, 2013)

Hydroclimatic changes in a climate‐sensitive tropical region - Dileep K. Panda; A. Kumar; R. B. Singandhupe; N. Sahoo (International Journal of Climatology, 2013)
In this study, the hydroclimatic variables of Orissa, a tropical region in eastern India, and the cyclonic disturbances over the Bay of Bengal were analysed to assess trends and variations using nonparametric statistical procedures. The trend results revealed pronounced warming pattern in the monthly maximum temperatures and cooling pattern in the monthly minimum temperatures for the period 1987–2001. The differential forcing mechanisms of greenhouse gases and aerosols were considered as a reason for the temperature extremes. For the period 1960–2003, significant upward shift was observed in June rainfall, particularly over the region where orography influences the rainfall. This study provides strong evidence suggesting the occurrence of abrupt shifts in the cyclonic disturbances over the Bay of Bengal. For the period 1901–2003, the monsoon depressions and cyclonic storms, which contribute a substantial amount of rainfall in Orissa and central India, exhibited significant downward abrupt shifts during 1971 and 1950, respectively. However, severe cyclonic storms in the post‐monsoon season showed significant upward shift during the 1961–1965 pentad. More cases of non‐significant decreasing trends were observed in the monsoon rainfall for the period 1980–2003 in spite of high inter‐annual variability. These trends may be attributed to the significant downward shift in the monsoon depression from 1983 onwards analysed for the period 1960–2003. Results also show that the observed trends are highly sensitive to the season of analysis and the period of records. Copyright © 2012 Royal Meteorological Society

Using InSAR to detect subsidence at brine wells, sinkhole sites, and mines - Michael L. Rucker; Bibhuti B. Panda; Robert A. Meyers; John C. Lommler (Carbonates and Evaporites, 2013)

Validation of Chlorophyll-a Algorithms in the Coastal Waters of Bay of Bengal Initial Validation Results from OCM-2 - P. V. Nagamani; M. I. Hussain; S. B. Choudhury; C. R. Panda; P. Sanghamitra; R. N. Kar; A. Das; I. V. Ramana; K. H. Rao (Journal of the Indian Society of Remote Sensing, 2013)

Microbial Biomass and Carbon Mineralization in Agricultural Soils as Affected by Pesticide Addition - Anjani Kumar; A. K. Nayak; Arvind K. Shukla; B. B. Panda; R. Raja; Mohammad Shahid; Rahul Tripathi; Sangita Mohanty; P. C. Rath (Bulletin of Environmental Contamination and Toxicology, 2012)

Managing terraced lowland and medium sloping land for sustainable agriculture: A study from the eastern ghat region of India - R. K. Panda; C. P. Arora; K. P. Gore; P. Jakhar; B. K. Dash (Irrigation and Drainage, 2011)
Judicious management of the terraced lowlands and adjacent medium‐sloping lands of the Eastern Ghat Region in India was addressed through a case study, in order to develop a sustainable agriculture package as a resource for poor tribal farmers. Quantification of available water resources during the period 2004–2007 revealed that average base flow and surface flow (as percentage of total rainfall) at a level of 37.2 and 34.7% respectively, could be made available in the study area, and would otherwise go out of the system without proper utilization. Economic resource conservation options for farmers, such as the management of paddy field riser bunds through construction of semi‐mechanical runoff disposal devices supplemented with a Eulaliopsis binata vegetative barrier, helped in reducing runoff and soil loss by 10.6% and 1.45 t ha ‐1 , respectively. Through paired t ‐tests at a 5% probability level, significant differences were observed in the reduction of the sediment yield, when comparing the proposed techniques with the farmers’ practices. Introduction of a promising HYV paddy cultivar (Oryza sativa L. or Lalat) fortified with the application of Gliricidia sepium leaves (grown on the periphery of the terraced lowlands) resulted in a paddy yield of 4.2 t ha ‐1 as against 1.7 t ha ‐1 obtained through the local paddy cultivar. Further, based on the availability of runoff water through a perennial stream, it was found that provision for a diversion irrigation channel constructed to harvest water would be a promising option for irrigating the adjacent medium‐sloping land for remunerative vegetable cultivation. Overall, the developed integrated package resulted in a cost–benefit ratio of 2.6:1 with a net present value of Rs. 116 000.00 (US$2900) at a 15% discount rate, increasing the scope for replicating this technology in other parts of the Eastern Ghat region. Copyright © 2011 John Wiley & Sons, Ltd.

Impact of bottom trawling on sediment characteristics—a study along inshore waters off Veraval coast, India - Usha Bhagirathan; B. Meenakumari; K. V. Jayalakshmy; S. K. Panda; V. R. Madhu; D. T. Vaghela (Environmental Monitoring and Assessment, 2010)

Use and variation of Pandanus tectorius Parkinson (P. fascicularis Lam.) along the coastline of Orissa, India - Kamal K. Panda; Anath B. Das; Brahma B. Panda (Genetic Resources and Crop Evolution, 2009)

Analysis of water and food security scenarios for 2025 with the PODIUM model: the case of Agro‐Ecological Region 12 of India - R. B. Singandhupe; P. Nanda; D. K. Panda; M. Swain (Irrigation and Drainage, 2008)
The Policy Interactive Dialogue Model (PODIUM), developed by the International Water Management Institute (IWMI), has been used to consider data of 1995 as a base to predict water–food security scenarios for 2025 of Agro‐Ecological Region 12 (AER12) of India having a total geographical area of 26.8 million ha. The model has been used to address the food and water security issues simultaneously and generates alternative scenarios highlighting the interlinkages between water and food security. In this study four scenarios: business as usual scenario (BAU); food security scenario (FS); water security scenario (WS); and water and food security scenario (WFS) have been analysed. The BAU scenario projects that the region AER12 of India will face a food deficit of 7.46 million t in 2025. The total annually renewable water resources of the region will be 40.3 billion m 3 in 2025, out of which a maximum of 21.7 billion m 3 will be available in Agro‐Ecological Sub Region (AESR12.1), followed by 10.2 and 8.3 billion m 3 in AESR12.2 and AESR12.3, respectively. The diversion of available water in all sectors (agriculture, domestic, industry) in AER12 was 15.4 billion m 3 in 1995, which is expected to increase by 81.7% in 2025, but due to urbanisation and industrial demand, the available water for the agricultural sector is expected to reduce by 64%. In the industry sector it is projected to jump from 10% in 1995 to 28% in 2025. After analysing the BAU scenario of the region, some of the specific alternative options have been explored with the PODIUM model by altering the drivers in order to find feasible ways to make the region secure and sustainable with a comfortable level of food and water by 2025. The outcomes of the alternative options are discussed in this paper. Copyright © 2008 John Wiley & Sons, Ltd.

Structural and Functional Analysis of Rice Catalase-B Gene Promoter: Presence of Dof and CAAT Binding Site - P. Mondal; N. Dey; A. K. Dash; A. Chatterjee; B. B. Sahu; B. Panda; I. B. Maiti; S. C. Sabat (Plant Molecular Biology Reporter, 2007)

Water Balance Simulation and Economic Analysis for Optimal Size of On-Farm Reservoir - B. Panigrahi; Sudhindra Nath Panda; A. Agrawal (Water Resources Management, 2005)

Total information content as an index of soil moisture - R. N. Sahoo; M. Bhavanarayana; B. C. Panda; C. N. Arika; R. Kaur (Journal of the Indian Society of Remote Sensing, 2005)

A water budget technique for the design of open drainage systems - Rabindra Kumar Panda; T. B. S. Rajput (Irrigation and Drainage, 2004)
A computer‐based water budget technique was developed considering the land gradient [{vertical interval between two adjacent field bunds (levees)=20 cm} ÷ the distance between the bunds] and paddy field bunds (viz. 16, 18, 20, 22, 24 cm) in its formulation for computing daily runoff from coastal paddy areas in India. The inputs used in the water budget technique consist of limited meteorological data that are easily available in India. The water budget technique was validated with the modified curve number method and the measured data collected during 2001 in a coastal paddy area of Orissa (east coast of India close to Bay of Bengal), India and its superiority was found. In most of the cases (barring a few events of 16 cm and 18 cm paddy field bunds for the water budget technique), statistically both methods differed significantly from each other while generating daily runoff. The estimate of the surface drainage coefficient (the amount of excess surface runoff water to be drained from the crop field during a 24‐hour period) for a 5‐year return period was computed as 100 mm day −1 (taking the 22 cm paddy field bund) and 109 mm day −1 in case of the water budget technique and modified curve number method, respectively. Copyright © 2004 John Wiley & Sons, Ltd.

Evaluating role of oxidative stress in determining the pathogenesis of falciparum malaria induced acute renal failure - Rachita Nanda; Pramila K. Mishra; U. K. Das; S. B. Rout; P. C. Mohapatra; A. Panda (Indian Journal of Clinical Biochemistry, 2004)

Differential antioxidant enzyme and thiol responses of tolerant and non-tolerant clones of Chloris barbata to cadmium-stress - Barnali Baisakhi; Jita Patra; Rabindra K. Panigrahy; Brahma B. Panda (Acta Physiologiae Plantarum, 2003)

Changes in antioxidant levels in Oryza sativa L. roots subjected to NaCl-salinity stress - M. H. Khan; Ksh L. B. Singha; S. K. Panda (Acta Physiologiae Plantarum, 2002)

Potato water use and yield under furrow irrigation - Panigrahi B.; Panda S.; Raghuwanshi N. (Irrigation Science, 2001)

A numerical technique for delineation of soil mapping units using multi-spectral remote sensing data - Ravinder Kaur; S K Bhadra; M Bhavanarayana; B C Panda (Journal of the Indian Society of Remote Sensing, 1998)

Monitoring and assessment of mercury pollution in the vicinity of a chloralkali plant. IV. Bioconcentration of mercury in in situ aquatic and terrestrial plants at Ganjam, India - Maheswar Lenka; Kamal K. Panda; Brahma B. Panda (Archives of Environmental Contamination and Toxicology, 1992)